EFL Teachers’ Immediacy and Professional Commitment on Students’ Boredom: A Review of Literature - Qin, Wen (Frontiers in Psychology, 2022)
Boredom is a psychological phenomenon that is defined as a state of hatred or incompatibility with any kind of repetitive experience in situations where liberation from instability is not possible and has several consequences. Boredom is one of the important causes of decreased motivation in EFL learners, and it is necessary to identify the factors affecting it. Therefore, this literature review addresses the state of boredom in relationship with teachers’ immediacy and professional commitment. Reviewing the literature has revealed that while teachers’ immediacy and professional commitments affect EFL learners’ boredom, other factors such as individual differences and environmental factors are in action. However, many studies confirmed that teachers play the most important role in decreasing or increasing learners’ state of boredom. The findings are significant for teacher educators to design more appropriate teacher education programs.